2020
DOI: 10.1186/s12889-020-09047-z
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective cross-sectional observational study on the epidemiological profile of dengue cases in Pernambuco state, Brazil, between 2015 and 2017

Abstract: Background: The spread of Dengue virus (DENV) infections, as well as their signs and symptoms, are the result of a complex interaction between several factors. In Brazil, especially in the Northeastern, dengue is an important public health problem. Here, we report an epidemiological analysis of dengue cases in Pernambuco state, Northeastern Brazil, during 2015-2017. Methods: This work is a retrospective cross-sectional observational study on the epidemiological profile of all dengue cases confirmed and reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 49 publications
1
5
0
14
Order By: Relevance
“…Recent studies demonstrated that immunity from previous ZIKV infections can neutralize subsequent DENV infections by all serotypes 26 , without exacerbating the severity of secondary heterologous infections by DENV 46 . This phenomenon could have led to higher numbers of asymptomatic or mild dengue cases 47 , resulting in low reporting of cases not only in Brazil, but also in most countries in the Americas, which experienced similar patterns of presumed low dengue cases after Zika outbreaks. Although the cross-protection of ZIKV-induced immunity on DENV infections may likely wane, its modulatory effects on DENV pathogenesis could not only explain the decline of dengue in 2017-2018, but also its resurgence in the following years, all over the Americas 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that immunity from previous ZIKV infections can neutralize subsequent DENV infections by all serotypes 26 , without exacerbating the severity of secondary heterologous infections by DENV 46 . This phenomenon could have led to higher numbers of asymptomatic or mild dengue cases 47 , resulting in low reporting of cases not only in Brazil, but also in most countries in the Americas, which experienced similar patterns of presumed low dengue cases after Zika outbreaks. Although the cross-protection of ZIKV-induced immunity on DENV infections may likely wane, its modulatory effects on DENV pathogenesis could not only explain the decline of dengue in 2017-2018, but also its resurgence in the following years, all over the Americas 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Low immunity is also a factor for DENV infection ( 36 ). One study associated mixed race with a greater likelihood of developing dengue than other ethnicities ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, different age groups have been described as the most related to dengue, e . g ., 15–49, 20–29, 21–30, 21–40, 30–39, 31–40, 18 years, ≥ 30 years or > 50 years [ 15 , 17 , 38 , 41 44 ]. These disagreements are probably influenced by the region/territory analyzed, as well as by the study design.…”
Section: Discussionmentioning
confidence: 99%